PENCETAKAN SERTIFIKAT VAKSIN OLEH PIHAK SWASTA - Satrio Wibowo (Legacy: Jurnal Hukum dan Perundang-Undangan, 2021)
The Covid-19 vaccination has started in Indonesia in early 2021, marked by the President of Indonesia as the recipient of the first dose of vaccine. After two weeks, it was continued with the second dose. Proof of being a person who has been vaccinated is receiving a vaccine certificate. This method of recording vaccine certificates uses the Population Identification Number (NIK) and the vaccine recipient's telephone number. The form of this certificate is a piece of paper that is very easily damaged, so some private parties offer certificate printing in a form that is easy to carry, not easily damaged, and practical to carry around. The problems raised in this study are the legality of the private sector in printing vaccination certificates and the legal consequences of printing vaccine certificates. The method used in analyzing is using empirical juridical research by observing the phenomena that occur and reviewing the laws and regulations relating to and regulating the Covid19 vaccine certificate. The study results stated that the printing of vaccine certificates by the private sector was not explicitly regulated in the legislation. It had room for the private sector for commercial purposes.